Price manipulation around seasoned equity offerings. - Lau, Yuk Ki. (2010)
In this paper, we investigate the possibility of establishing a manipulative equilibrium when a firm announces a seasoned equity offering (SEO) to raise funds for investing in a probable project. We assume that the project has a high probability of downside performance and low probability of a strong upside, hence, negative net present value (NPV) on average. We find that under certain conditions, a potentially informed speculator who holds a portion of the internal equity may find it profitable to trade even when he does not have any information about the true state of the project, possibly causing the firm to invest when it has not received any public signal. The effect of the informed speculator's trading is also shown in the SEO price set by the market maker by making use of the principles of Bayesian theory.